(untitled) (Acta Judicial Journal, 2018)
In this article we will analyze the most relevant issues of International Law and Procedural Law in the Statute of the Victim, Law 4/2015 of April 27 -in effect from October 28, 2015-, Law that includes in its articles the rights of victims of crimes, both procedural and extraprocess. Likewise, the important functions of information and judicial protection of fundamental rights that it text attributes to the Judicial Administration Counselor will be highlighted. In effect, the Victim Statute Law is divided into the following sections: information, protection, participation and support. Special emphasis will be placed on the rights of especially vulnerable victims and minors and on the role that the Judicial Administration Counselor, as a full member of the Court of Justice, assumes in relation to the protection.